Pesticides : return to sender! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Ethiopia is the second country in Africa, after Morocco, to be saddled with obsolete pesticides, totalling 1,500 tonnes stockpiled in more than 400 sites, which are often near local communities. A FAO project, financed by USAID, plans to move the...